Copper-Catalyzed Three-Component Oxytrifluoromethylation of Alkenes with Sodium Trifluoromethanesulfinate and Hydroxamic Acid - Jiang, Xin-Yi; Qing, Feng-Ling (Angewandte Chemie International Edition, 2013)
Radical paths: The title reaction of olefins with NaSO2CF3 and N‐hydroxy‐N‐phenylacetamide at room temperature is described for the first time (see scheme). This reaction provides a practical and convenient route to a series of trifluoromethylated alcohols bearing a wide range of functional groups.